Analisis Strategi Pemasaran Menggunakan Matriks SWOT Dalam Meningkatkan Jumlah Pengguna pada Aplikasi Halodoc di Masa Pandemi - Alan Nathanael K; Ety Dwi Susanti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the state of a business in the era of the COVID-19 pandemic, whether these business people experienced a decline or experienced an increase in sales. The object of our research as this research is the Halodoc application, which is engaged in the health sector which makes it easy for users to get health services with a smartphone application only. The data collection technique that we used in this study was using observation, in-depth interviews with relevant sources and documentation. The data sources in our research are Business Development from the Halodoc application and Halodoc application users who have made transactions. To analyze the data obtained, we used a SWOT analysis technique and the Halodoc application was in quadrant I. In the sense that the Halodoc application supports using an aggressive strategy, the company has more strength to face a business threat in the future when compared to their weaknesses. Therefore, during the current COVID-19 pandemic, in particular, the Halodoc application is one of the companies that gets very significant benefits when compared to other business sectors. Keywords: Marketing Strategy, SWOT Analysis, Covid-19